Forming of individual mathematical models of working processes of gas turbine engines - Королев, П. В. (Proceedings of National Aviation University (archive), 2000)
A procedure for obtaining individual models of working process of gas-turbine engines is proposed; such models are the base of effective algorithms of control of maintenance of stocks of engines. fl-36 aviation engine was taken as an example to illustrate the possibilities of realization of the procedure